2017
DOI: 10.1016/s2213-8587(17)30061-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term incidence of microvascular disease after bariatric surgery or usual care in patients with obesity, stratified by baseline glycaemic status: a post-hoc analysis of participants from the Swedish Obese Subjects study

Abstract: Summary Background Bariatric surgery in patients with obesity and type 2 diabetes is associated with diabetes remission and prevention of complications. The long-term effects of bariatric surgery on microvascular complications in patients with prediabetes are unknown. Methods The prospective, matched Swedish Obese Subjects study examines outcomes after bariatric surgery. Patients were recruited between September 1, 1987, and January 31, 2001. Age was 37–60 years and BMI was ≥34 kg/m2 in men and ≥38 kg/m2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 35 publications
6
78
1
4
Order By: Relevance
“…According a recent study, having bariatric surgery being done in addition to intensive medical therapy for the treatment of type 2 diabetes in patients with BMI 27-43, yielded significant results in the reduction and sometimes resolving of diabetes compared to intensive medical therapy alone [12]. Another recent study showed that the risk of microvascular complications is reduced due to improved glycemic control in pre diabetic patients who undergo bariatric surgery [13].…”
Section: Discussionmentioning
confidence: 99%
“…According a recent study, having bariatric surgery being done in addition to intensive medical therapy for the treatment of type 2 diabetes in patients with BMI 27-43, yielded significant results in the reduction and sometimes resolving of diabetes compared to intensive medical therapy alone [12]. Another recent study showed that the risk of microvascular complications is reduced due to improved glycemic control in pre diabetic patients who undergo bariatric surgery [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ideal time point for considering metabolic surgery needs to be defined and likely also depends on the comorbidities present. T2DM is a good example: patients with long-term T2DM and a need for insulin therapy have a much lesser likelihood for diabetes remission than patients with an impaired glucose tolerance [2,18,19]. Based on the EOSS, a patient with insulin therapy and a high insulin dose would be graded as EOSS 2 or 3, depending on the severity of the diabetic complications.…”
Section: Assessment Of Patients Suitable For Metabolic Surgerymentioning
confidence: 99%
“…Hence, one could argue that even patients with T2DM and EOSS 1 should be considered for metabolic surgery since they would be likely to receive the strongest benefit. The importance of operating earlier rather than later is further supported by the findings of the SOS study, which shows that metabolic surgery has a lower impact on the reduction of macro- and microvascular events the longer the T2DM existed prior to surgery [2,18]. In contrast, a recent meta-analysis did not find a relationship between the duration of T2DM and the efficacy of metabolic operations regarding the reduced incidence or improvement of microvascular complications [8].…”
Section: Assessment Of Patients Suitable For Metabolic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,5 NHANES is a programme of population-based studies designed to assess the health of adults and children in the United States. For the current analysis, Ali and colleagues used NHANES data from 1988-1994, 1999-2004, 2005-2010 and 2011-2014 Some of the findings from the analysis conducted by Ali and colleagues also imply that any additional cardiovascular benefits from targeting specifically pre-diabetic individuals would be modest.…”
mentioning
confidence: 99%